1974
DOI: 10.1090/s0002-9947-1974-0356068-3
|View full text |Cite
|
Sign up to set email alerts
|

Semicellularity, decompositions and mappings in manifolds

Abstract: If X is an arbitrary compact set in a manifold, we give algebraic criteria on X and on its embedding to determine that X has an arbitrarily small, closed neighborhood each component of which is a p-connected, piecewise linear manifold which collapses to a ^-dimensional subpolyhedron from some p and q. This property generalizes cellularity.The criteria are in terms of UV properties and Alexander-Spanier cohomology.These criteria are then applied to decide when the components of a given compact set in a manifold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…By [C,Corollary 13] there is a map/: S2k+X -> S2*+1 such that one point inverse is a A:-sphere, the other nondegenerate point inverses are (k -l)-connected polyhedra, and the image of the nondegenerate point inverses is a tame arc A. Let g: S2k+X -> Sk+X be a Ar-sphere mapping [L4], [C-D4], [F-W].…”
mentioning
confidence: 99%
“…By [C,Corollary 13] there is a map/: S2k+X -> S2*+1 such that one point inverse is a A:-sphere, the other nondegenerate point inverses are (k -l)-connected polyhedra, and the image of the nondegenerate point inverses is a tame arc A. Let g: S2k+X -> Sk+X be a Ar-sphere mapping [L4], [C-D4], [F-W].…”
mentioning
confidence: 99%
“…Introduction. Bing [Bi;m = 3], Bean [Be;777 = 3], and Coram [Co;m > 4] showed that if A" is a proper, closed subset of a PL manifold Mm such that for each open, connected subset U C M either U -(X n U) is connected or X n bd(U) ¥=0, then there is a monotone mapping/from M onto the m-sphere with each component of X being a point-inverse of /. These results are generalized in two ways.…”
mentioning
confidence: 99%
“…Beginning with McMillan's cellularity criterion [17], loop shrinking conditions have proven useful in the study of compacta wildly embedded in PL manifolds. The cellularity criterion was applied to embeddings of non cell-like compacta in [5], [6], [10], [ll], [20], [21], and Daverman [8] used a similar condition to study embeddings of S . In this paper…”
mentioning
confidence: 99%